Influence of Ni-Fe load in a bimetallic catalyst supported on Zeolite 13X for CO2 methanation in a fixed bed reactor - Mercader Plou, Víctor Daniel; Ruiz-Alejos, David; de Jong, Wiebren; Durán, Paul; Aragüés Aldea, Pablo; Sanz Monreal, Pablo; Becerril, Miguel Ángel; Francés, Eva; Herguido, Javier; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2024)
In this work three Ni-Fe catalysts supported on zeolite 13X were tested for CO2 methanation at different temperatures. The study shows the influence of the active species load on the synthesized catalysts. In addition, the effect of Ni-Fe ratio present on the catalysts was observed.